2019
DOI: 10.3390/healthcare7020062
|View full text |Cite
|
Sign up to set email alerts
|

Review of Programs for Persons Facing Death with Dementia

Abstract: Background: Persons with advanced dementia cannot initiate activities because of the executive dysfunction. The lack of activities was identified as one of the most important factors contributing to behavioral problems of these persons. The unmet needs were boredom/sensory deprivation, loneliness/need for social interaction, and need for meaningful activities. There is a need for activities designed specifically for residents with advanced dementia. Objective: A description of patient’s needs and of programs t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 49 publications
(57 reference statements)
0
14
0
Order By: Relevance
“…Accordingly, our study provides empirical evidence regarding the heterogeneity of BPSD [ 13 - 15 ] by revealing the distinct underlying predictors for the seven BPSD subsyndromes. Results showed that there were multiple predictors of all BPSD; however, the mechanisms underlying how a set of neurobiological, psychosocial, and environmental factors interplay and subsequently result in specific symptoms remain elusive [ 72 ].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Accordingly, our study provides empirical evidence regarding the heterogeneity of BPSD [ 13 - 15 ] by revealing the distinct underlying predictors for the seven BPSD subsyndromes. Results showed that there were multiple predictors of all BPSD; however, the mechanisms underlying how a set of neurobiological, psychosocial, and environmental factors interplay and subsequently result in specific symptoms remain elusive [ 72 ].…”
Section: Discussionmentioning
confidence: 84%
“…Although BPSD are associated with neurological mechanisms of neurocognitive disease to some extent, previous studies have revealed that the actual occurrence of symptoms can be attributed to diverse personal factors (eg, medical conditions, premorbid personality, and physical and psychological unmet needs), social factors (eg, communication with caregivers, caregivers' stress and depression, and lack of social activities), and environmental factors (eg, overstimulation and lack of established routines), rather than to neurocognitive impairment alone [11,12]. While a few studies have provided evidence that supports frequent co-occurrence of individual BPSD, others have contended that BPSD are distinct and heterogeneous and have different determinants and consequences [13][14][15]. Determining key factors that predict the different types of BPSD is the first step, since it would guide the determination of which strategies should be chosen to target the underlying causes and ultimately prevent or manage the symptoms [12,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, our study provides empirical evidence regarding the heterogeneity of BPSD [13][14][15] by revealing the distinct underlying predictors for the seven BPSD subsyndromes. Results showed that there were multiple predictors of all BPSD; however, the mechanisms underlying how a set of neurobiological, psychosocial, and environmental factors interplay and subsequently result in specific symptoms remain elusive [72].…”
Section: Implications For Different Approaches To Heterogeneous Bpsd Subsyndromesmentioning
confidence: 78%
“…Finding ways to connect, communicate and engage people living with dementia to mitigate the symptoms of advancing cognitive decline is crucial for quality of life (Volicer, 2019). Caregivers and families are also impacted by dementia (Allen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%